Prevalence and causes of vision loss in North Africa and Middle East in 2015: magnitude, temporal trends and projections - Kahloun, Rim; Jonas, Jost B. (British journal of ophthalmology, 2019)
BACKGROUND: To assess the prevalence and causes of vision impairment in North Africa and the Middle East (NAME) from 1990 to 2015 and to forecast projections for 2020. - METHODS: Based on a systematic review of medical literature, the prevalence of blindness (presenting visual acuity (PVA) <3/60 in the better eye), moderate and severe vision impairment (MSVI; PVA <6/18 but ≥3/60) and mild vision impairment (PVA <6/12 but ≥6/18) was estimated for 2015 and 2020. - RESULTS: The age-standardised prevalence of blindness and MSVI for all ages and genders decreased from 1990 to 2015, from 1.72 (0.53-3.13) to 0.95% (0.32%-1.71%), and from 6.66 (3.09-10.69) to 4.62% (2.21%-7.33%), respectively, with slightly higher figures for women than men. Cataract was the most common cause of blindness in 1990 and 2015, followed by uncorrected refractive error. Uncorrected refractive error was the leading cause of MSVI in the NAME region in 1990 and 2015, followed by cataract. A reduction in the proportions of blindness and MSVI due to cataract, corneal opacity and trachoma is predicted by 2020. Conversely, an increase in the proportion of blindness attributable to uncorrected refractive error, glaucoma, age-related macular degeneration and diabetic retinopathy is expected. - CONCLUSIONS: In 2015 cataract and uncorrected refractive error were the major causes of vision loss in the NAME region. Proportions of vision impairment from cataract, corneal opacity and trachoma are expected to decrease by 2020, and those from uncorrected refractive error, glaucoma, diabetic retinopathy and age-related macular degeneration are predicted to increase by 2020.